Do we need better information to advise women with stress incontinence on their choice of surgery? Report from the ICI‐RS 2018. (10th December 2019) - Giarenis, Ilias; Malde, Sachin; Harding, Christopher; Robinson, Dudley; Gajewski, Jerzy; Rahnamai, Mohammad; Cardozo, Linda
Abstract: Aims: The regulatory warnings about the safety of the synthetic midurethral slings (MUS) had a significant effect on how patients and physicians approach surgical management of stress urinary incontinence (SUI). In this changing landscape, the purpose of this research Think Tank (TT) was to provide an update of the current knowledge about the safety and efficacy of SUI surgery, to review patient goals and expectations and to identify factors affecting the decision making for surgery. Methods: This is a consensus report of the proceedings of TT3: "Do we need better information to advise women with stress incontinence on their choice of surgery?" from the annual International Consultation on Incontinence‐Research Society (ICI‐RS), June 2018. Results: Despite the body of evidence supporting the continued use of MUS, the short follow‐up of most of the studies and the lack of "real life" data regarding pain and sexual dysfunction make the development of recommendations challenging. Women with SUI are often happy to "trade" efficacy for a procedure with less associated morbidity and therefore it is not always the procedure with the highest success rate that is ultimately chosen. However, a number of factors influence treatment decision and there is limited evidence about what level of all these factors women are willing to tolerate for a given success rate, or how much success they are willing to trade for a lower complication rate. Conclusions: The ICI‐RS proposed research questions which may be able to assist in improving the counseling and management of women with SUI.